Applying Enhanced Recovery Pathways to Unique Patient Populations - Lee, Grace C.; Hodin, Richard A. (Clinics in Colon and Rectal Surgery, 2019)
Enhanced Recovery after Surgery (ERAS) pathways have become popular in colorectal surgery due to their associated decrease in length of stay (LOS), complications, and readmission rate. However, it is unclear if these pathways are safe, feasible, or effective in unique patient populations such as elderly patients, urgent/emergent surgeries, patients with specific comorbidities, inflammatory bowel disease, or pediatric patients. Enhanced recovery pathways appear safe in elderly patients, associated with decreased complications, though with slightly lower rates of adherence and increased LOS and readmission rates. Modified ERAS pathways have been applied to urgent and emergent surgeries, resulting in decreased morbidity and LOS. There have been no studies that performed subgroup analyses of ERAS pathways in patients with specific comorbidities. Studies investigating patients with inflammatory bowel disease on enhanced recovery pathways are extremely limited, but suggest that they are safe and feasible. Data on ERAS pathways in pediatric patients are still emerging. Therefore, though data are sparse, enhanced recovery pathways appear to be safe in unique patient populations, with similar efficacy in decreasing LOS and complications. There is an urgent need for more studies investigating these specific patient groups to aid perioperative decision making by colorectal surgeons.
Keywords: ERAS; enhanced recovery; elderly; urgent; pediatric